2008
DOI: 10.1016/j.brat.2007.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Reducing emergency medical service use in patients with chronic psychotic disorders: Results from the FAST intervention study

Abstract: Patients with schizophrenia have disproportionately high rates of emergency medical service use, likely contributing to the high cost this illness places on society. The aim of this study was to examine the impact of a theory-based, behavioral intervention on immediate and long-term use of emergency medical services. Older patients with schizophrenia (N=240) were randomized to receive either a behavioral, skills-building intervention known as Functional Adaptation and Skills Training (FAST) or to a time equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…The introduction of more effective treatments, including new drug therapies, have played a role in reducing the average duration of hospitalisation for patients with schizophrenia. Thus the contribution of ER admissions to overall resource use, which has largely been overlooked in favour of hospital stays of 41 day duration, has increasing relevance to overall schizophrenia care and costs 34 . This is evident from the high proportion of patients in both patient cohorts requiring ER treatment during the retrospective and first prospective years.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of more effective treatments, including new drug therapies, have played a role in reducing the average duration of hospitalisation for patients with schizophrenia. Thus the contribution of ER admissions to overall resource use, which has largely been overlooked in favour of hospital stays of 41 day duration, has increasing relevance to overall schizophrenia care and costs 34 . This is evident from the high proportion of patients in both patient cohorts requiring ER treatment during the retrospective and first prospective years.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] A recent randomized trial of a behavioral/skills-building intervention found short-term decreases in ED use among older patients with schizophrenia. [ 29 ] Clearly, future research will continue to show that the ED can serve as an important identification site for cost-effective intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published report on a randomized trial (older patients [n = 240] with schizophrenia age 40 and older) found that FAST participants showed significant improvement in social skills and everyday functional skills compared to an attention controlled group. In addition, FAST participants were almost half as likely to use emergency medical services during the active six-month treatment phase of the study, though no difference in service use was found in the subsequent year of follow-up [17*]. …”
Section: Psychosocial Rehabilitation In Older Adults With Serious Menmentioning
confidence: 99%